Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak - Ockelmann, Kurt W.; Cedhagen, Tomas (European Journal of Taxonomy, 2019)
Small usually beautifully coloured mussels from the Kattegat were to date identified as Modiolus adriaticus (Lamarck, 1819) since C.G.Johs. Petersen’s account of the shell-bearing molluscs was published in 1888. However, these mussels from Danish and Swedish waters represent a very distinct new species which also is endemic. The present paper serves to describe this new species, Modiolus cimbricus sp. nov., which belongs to the genus Modiolus Lamarck, 1799. The genus Gibbomodiola Sacco, 1898, to which Modiolus adriaticus has been moved, is here synonymized with Modiolus Lamarck, 1799.